PENGEMBANGAN MEDIA PEMBELAJARAN “KARTU NUSANTARA” PADA MATERI KERAGAMAN SUKU BANGSA KELAS IV SDN REJOAGUNG 3 NGORO JOMBANG - Adila, Salsabela Nur; Fitra Raharja, Hawwin; Rizqi Salamah, Evi (IJPSE Indonesian Journal of Primary Science Education, 2024)
This research is a typeof development research using the ADDIE model which includes Analysis, Design, Development, Implementation, Evaluation. This model is used to solve the problem of developing the "Nusantara Card" learning media on class IV ethnic diversity material at SDN Rejoagung 3 Ngoro Jombang. The subjects of this research were fourth grade students with a total of 18 students. Data analysis techniques using field notes, validator questionnaires and student response questionnaires. Recapitulation of Media and Material Validation. The researcher concluded that the feasibility of the "NUSANTARA KARTU" a score of 98.17 with very valid criteria. Quantitative data from the questionnaire obtained a total score of 1080 on the maximum score and an average of 60, a score of 1031 on the obtained score with an average of 57.2, and a score of 1718.1% on the percentage with an average of 95.45%. With these values, a large-scale trial using the Nusantara Card learning media, material on ethnic diversity, obtained very interesting criteria. it can be concluded that the Nusantara Card media can be well received and applied to material on ethnic diversity.